Aligning Corporate Strategies with the Sustainable Development Goals - Kashan Pirzada; Kamran Ahmed; Gabriel Moens (Foresight and STI Governance)
The introductory paper of this special issue examines general issues of synthesizing the corporate strategies with the sustainable development goals (SDGs), as well as knowledge generation and adoption of new technologies to achieve SDGs. In the next section of this editorial, we summarise the eight papers included in this special issue. We conclude the editorial by offering insights for future research in this area.